Technology Adoption Segmentation of MSMEs in Border Areas using TRI and Hierarchical Clustering - Fadlan, Muhammad; Muhammad, Muhammad; Suprianto, Suprianto; Hadriansa, Hadriansa; Ilyas, Arifai (ISB Atma Luhur, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in border areas such as Nunukan-Sebatik often face challenges in adopting modern technologies, which hinder their growth and competitiveness. This study employs a segmentation approach using agglomerative hierarchical clustering based on the Technology Readiness Index (TRI) to segment MSMEs in border areas and develop targeted strategies to accelerate technology adoption. A hierarchical clustering technique is applied to segment MSMEs according to their technology readiness levels. Data on technology readiness were collected through surveys, and the clustering results were analyzed to identify distinct MSME groups. The TRI score was 3.72, indicating a high level of technology readiness, which suggests that many MSMEs are open to technological innovation into their daily operations. The results also reveal that MSMEs in Nunukan-Sebatik can be grouped into two clusters based on hierarchical clustering: Cluster 1, which consists of MSMEs that are more prepared and optimistic about technology adoption, and Cluster 2, which faces significant challenges. These findings highlight a digital readiness gap among MSMEs, where only a tiny portion (Cluster 1) is fully prepared, while the majority (Cluster 2) still encounters barriers to adoption.